Social capital development after migration: The role of employment, children and gender factors for Russian post-2022 migrants - Vladimir Kozlov; Ekaterina Sokolova; Olga Veselovskaya; Daria Saitova (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2024)
A significant part of Russian migrants, who fled the country after February 2022, are qualified professionals, and almost half have moved with their partners and children. For them, the social capital required for integration in the host country is closely linked to family issues and daily routines. Defining social capital as a combination of relationships and attitudes, this study examines the role of employment, children, and gender in its development after migration. Empirical data were obtained from online surveys conducted among Russian migrants around the world, as well as among those who stayed in Russia. Quantitative analysis of the data shows that employment, children, and gender are related to the formation of migrants' social capital. In addition to the role of employment, we show that in migration women are more sociable and open to interaction, and having children widens their social circle and increases the number of acquaintances, which in turn contributes to the formation of social capital. Based on the above, it can be concluded that migrant families with children have a great potential for integration into the host society.
Keywords: F22; J12; J13; J15; I31; 330; Migration; social capital; integration; families; gender